Rational Design Protein Engineering Through Crowdsourcing - Farmer, Tylar Seiya; Bohse, Patrick; Kerr, Dianne (Journal of Student Research, 2018)
Two popular methods exist to engineer a protein: directed evolution and rational design. Directed evolution utilizes a controlled environment to create proteins through induced mutations and selection, while rational design makes desired changes to a protein by directly manipulating its amino acids. Directed evolution is currently more commonly used, since rational design relies on structural knowledge of the protein of interest, which is often unavailable. Utilizing crowdsourcing manpower and computational power to improve protein depictions allows rational design to be more easily used to perform the manipulation of proteins. Two free programs, “Folding@home and “Foldit”, allow anyone with a computer and internet access to contribute to protein engineering. Folding@home relies on one’s computational power, while Foldit relies on user intuition to improve protein models. Rational design has allowed protein engineers to create artificial proteins that can be applied to the treatment of illnesses, research of enzyme activity in a living system, genetic engineering, and biological warfare. Starting with an overview of protein engineering, this paper discusses the methods of rational design and directed evolutions and goes on to explain how computer based programs can help in the advancement of rational design as a protein engineering method. Furthermore, this paper discusses the application of computer based programs in medicine and genetic engineering and presents some ethical issues that may arise from using such technology. The paper concludes with an analysis of whether or not computer based programs for protein engineering is worth the investment.